Editorial Introduction to new directions in gender research—2nd edition - Santos, M. H.; Cerqueira, C. (Social Sciences, 2024)
The second edition of the Special Issue “New Directions in Gender Research” includes 13 articles from diverse disciplinary fields, applying multiple methodologies. This issue reflects the vitality of the disciplinary field of gender studies that crosses theoretical and epistemological approaches. It should also be emphasized that the diversity of empirical studies presented in this issue shows that gender studies cover a multitude of topics. These often reveal a social relevance in addition to their scientific pertinence.